Legal Consequences of Refugees’ Visa Misuse to Obtain Indonesian Citizenship - Aninda Novedia Esafrin; Antikowati Antikowati; Gautama Budi Arundhati (Faculty of Law, University of Jember, Indonesia, 2020)
This paper aims to examine problems regarding the possible abuse by refugees inconsistent with Indonesia’s laws and regulations. In the context, the government can make efforts to deal with refugees who enter Indonesia illegally and the government can formulate new laws and regulations that can discuss problems caused by refugee actions in more detail, clearly and in detail, starting from the arrest process to the sanctions process that is obtained. Because until now Indonesia has not had this policy. Those refugees' status then serves the purpose to get a decent living in a recipient country such as Australia. Misuse of visas is widely used by refugees because Indonesia implements a visa-free system of visits to 169 countries in the world. Visa-Free Visit Policy based on President Regulation Number 125 of 2016 concerning Visa-Free Visit. In this regard, the country needs to anticipate the increasing number of visa misuse for refugees entry to Indonesian territory by sending them to immigration detention centers as a form of sanctions imposed before returning to their country and making deportation the last step in resolving the visa misuse problem committed by refugees. KEYWORDS: misuse of visa in Indonesia, immigration detention, refugee deportation.